Biotechnological characterization of a diverse set of wheat progenitors (Aegilops sp. and Triticum sp.) using callus culture parameters. Issue 1 (14th August 2015) - Özgen, Murat; Birsin, Melahat A.; Benlioglu, Berk
Abstract : It is known that genetic diversity is the most important factor in classical and modern plant breeding. The considerable increase in the number of transgenic crops reveals the value of new plant genetic resources. In this study, a set of 12 wheat progenitors were screened for tissue culture parameters such as callus induction, callus weight, regeneration capacity of callus and callus efficiency using mature embryos. Embryos were excised from imbibed seeds of the progenitors. The excised embryos were placed scutellum upwards in dishes containing 2 mg/l 2, 4-dichlorophenoxyacetic acid (2, 4-D) for callus induction. The developed calli and regenerated plants were maintained on 2, 4-D free MS medium. When mature embryos of 12 wheat progenitors ( Aegilops sp. and Triticum sp.) were compared, significant differences were detected in callus induction frequency, weight of callus, regeneration capacity and culture efficiency. A significant genotypic effect was observed on the culture responses. Of the 12 wheat progenitors tested, Aegilops umbellulata had the highest regeneration capacity of callus. Aegilops biuncialis created the most regenerable calli because of the highest callus induction and culture efficiency. In the experiment, callus induction was significantly correlated with callus weight ( r = 0.820) and regeneration capacity ( r = 0.955). Weight of callus was significantly correlated with regeneration capacity ( r = 0.740), while there was no significant correlation between callus induction frequency and culture efficiency ( r = 0.350). Our results showed that, generally, mature embryos of some Aegilops and Triticum species have a high regeneration capacity, and therefore, can be used as an effective explant source for the successful application of biotechnology in crop improvement.